Pengembangan Strategi Pembelajaran PJOK Inovatif dan Efektif di Sekolah Menengah Atas : Studi Kasus di SMAN 2 Kotabumi - Serunting, Putri Sabila Syifa Buay; Bhakti, Yopi Hutomo; Suhariyanti, Mela (MAN Insan Cendekia Jambi, 2025)
This study aims to identify strategies and challenges in learning Physical Education, Sports, and Health (PJOK) at SMAN 2 Kotabumi. Qualitative research methods were used with data collection techniques through observation, interviews, and documentation. The results showed that the effective learning strategy of PJOK is by using activity-based learning methods and utilizing existing facilities and resources, thus producing effective learning and innovation. However, there are several challenges faced, the zoning policy affects the social heterogeneity of students and the lack of motivation to learn Pjok, so students are less enthusiastic because it is less challenging. The conclusion of the study is that to overcome this, student teaching assistants apply innovative approach strategies such as the befriending approach, ice breaking, and individualized evaluation. This research is expected to contribute to the development of more effective and efficient PJOK learning strategies. Thus, this research can help improve the quality of PJOK learning at SMAN 2 Kotabumi and other schools. This research also provides recommendations to improve the quality of PJOK learning.